Vulnerability assessment of the coastal wetlands in the Yangtze Estuary, China to sea-level rise. (5th April 2015) - Cui, Lifang; Ge, Zhenming; Yuan, Lin; Zhang, Liquan
Abstract: Sea-level rise (SLR) caused by global climate change will have significant impacts on the low-lying coastal zone. The coastal wetlands in the Yangtze Estuary, with their low elevation, are particularly sensitive to SLR. In this study, the potential impacts of SLR on the coastal wetlands in the Yangtze Estuary were analyzed by adopting the SPRC (Source–Pathway–Receptor–Consequence) model. Based on the SPRC model and IPCC vulnerability definition, an indicator system for vulnerability assessment on the coastal wetlands to SLR was developed, in which the rate of SLR, subsidence rate, habitat elevation, mean daily inundation duration of habitat and sedimentation rate were selected as the key indicators. A spatial assessment method based on a GIS platform was established by quantifying each indicator, calculating the vulnerability index and grading the vulnerability. Vulnerability assessment, based on the projection of SLR rates from the present trend (0.26 cm/yr) and IPCC's A1 F1 scenario (0.59 cm/yr), were performed for three time periods: short-term (2030s), medium-term (2050s) and long-term (2100s). The results indicated that in the 2030s, 6.6% and 9.0% of the coastal wetlands were within the grade of low vulnerability under the scenarios of present trend and A1 F1, respectively. In the 2050s, the percentage of coastal wetlands within the grades of low and moderate vulnerability increases to 9.8% and 0.2%, 9.5% and 1.0% under the scenarios of present trend and A1 F1, respectively. In the 2100s, 8.1% and 3.0% of the coastal wetlands were within the grade of low vulnerability, 0.8% and 2.8% were within the grade of moderate vulnerability under the scenarios of present trend and A1 F1, respectively. The percentage of coastal wetlands within the grade of high vulnerability increases significantly, amounting to 2.3% and 6.9% under the scenarios of present trend and A1 F1, respectively. The application of the SPRC model, the methodology developed and the results could assist with the objective and quantitative assessment of the vulnerability of coastal wetlands undergoing the impacts of SLR elsewhere. Without proper mitigation measures, the potential decrease in the area and loss of habitats and ecosystem services from the wetlands is inevitable. Based on the results of this study, mitigation measures should be considered for securing the future of the coastal wetlands in the Yangtze Estuary, which include the management of sedimentation, rehabilitation and re-creation of wetland habitat, reduction of land subsidence and control of reclamation. Highlights: Vulnerability assessment on the wetlands in the Yangtze Estuary under sea-level rise. An SPRC model was adopted to analyze the potential impacts. An indicator system for vulnerability assessment on coastal wetlands was developed. An assessment under the two scenarios of sea-level rise for short, medium and long terms. Mitigation measures should be considered to conserve the coastal wetlands.